Pediatric Obesity and the Immune System - Umano, Giuseppina Rosaria; Pistone, Carmelo; Tondina, Enrico; Moiraghi, Alice; Lauretta, Daria; Miraglia del Giudice, Emanuele; Brambilla, Ilaria (Frontiers in Pediatrics, 2019)
Obesity has reached pandemic proportion and represents a major risk for several comorbidities. In addition to metabolic and cardiovascular obesity-related diseases, recent evidence suggested that obesity might affect immune system function. Adipose tissue is considered an endocrine organ that actively secretes cytokines also referred to as “adipokines.” Adipokines play an important role in the control of human metabolism. The dysfunctional adipose tissue in obese individuals is characterized by an altered cytokine secretion pattern that promotes chronic low-grade inflammation. Epidemiological evidence highlights the association between obesity and allergic and immune-mediated diseases, such as asthma, allergic rhinitis, rheumatic arthritis, and psoriasis. Less is known about underlying pathogenic mechanisms. However, several recent in vivo and in vitro studies have reported that adipokines are involved in inflammatory and autoimmune disorders by influencing both innate and acquired immune responses. In addition, obesity has been associated with reduced immune surveillance and increased risk of cancer. This paper reviews the evidence regarding the role of adipokines in immune system regulation, with particular emphasis on autoimmune, allergic, and inflammatory disorders. Understanding how obesity affects immune system functions may enable researchers to find new potential therapeutic targets in the management of allergic and autoimmune diseases.